Defining Museums of Contemporary Art: the Phenomenon of Their Popularity in Recent Decades - Shalina, Natalia (Actual Problems of Theory and History of Art, 2015)
The aim of this research is to understand what a museum of contemporary art is and what makes it different from other art museums. This research is an attempt to outline characteristic features of museums of contemporary art, which way they are understood by their visitors, and to reveal some positive and negative aspects from the position of visitors. The methodology used to achieve this goal was based on a survey, in which respondents were questioned about their interest towards contemporary art and their experience of visiting museums of contemporary art (geographical frames of the research included countries of EU and Latin America, Russia, USA and Japan). According to the results, people tended to stress three main features that distinguished museums of contemporary art from other museums. These features included contemporary art and its interpretation in museum space, interactive approach to learning and architecture of museum buildings. Every aspect was explored more in depth. Tight connection between high level of popularity of museums of contemporary art and the development of tourist industry through the two last decades was revealed. This correlation between cultural and economic spheres allows looking at museums of contemporary art at the angle of economic changes in society, and forms a basis for a further research.
Keywords: museum of contemporary art; museum of modern art; Bilbao effect; museum audience; interactivity in museum; museum space; museum architecture; contemporary museum architecture; Tate Modern; MOMA